2022
DOI: 10.4093/dmj.2021.0195
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-Binding Protein 4 in Patients with and without Diabetic Retinopathy

Abstract: Background: Fatty acid-binding protein 4 (FABP4) has been demonstrated to be a predictor of early diabetic nephropathy. However, little is known about the relationship between FABP4 and diabetic retinopathy (DR). This study explored the value of FABP4 as a biomarker of DR in patients with type 2 diabetes mellitus (T2DM).Methods: A total of 238 subjects were enrolled, including 20 healthy controls and 218 T2DM patients. Serum FABP4 levels were measured using a sandwich enzyme-linked immunosorbent assay. The gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…There is a positive association of FABP4 with obesity [ 27 ] and T2DM [ 28 ]. The results in our study were consistent with the previous study [ 29 ], displaying that FABP4 was positively related to DR severity in patients with T2DM. A 5-year prospective cohort study demonstrated a positive association of baseline FABP4 with DR, and its severity developed in the future [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…There is a positive association of FABP4 with obesity [ 27 ] and T2DM [ 28 ]. The results in our study were consistent with the previous study [ 29 ], displaying that FABP4 was positively related to DR severity in patients with T2DM. A 5-year prospective cohort study demonstrated a positive association of baseline FABP4 with DR, and its severity developed in the future [ 10 ].…”
Section: Discussionsupporting
confidence: 93%